RANCANG BANGUN SISTEM INFORMASI AKUNTANSI SIKLUS PERSEDIAAN PADA RUMAH SAKIT - Setianingrum, Liya Anggraini (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2021)
Hospital is one of the business areas that every year required accountability report to the company leadership in the form of financial statements. The purpose of this research is to design an accounting information system inventory cycle on the procurement of drugs and medical devices in accordance with applicable standards and tailored to the needs of Hospital. This research uses descriptive qualitative method that provides an overview related to the design of accounting information system in accordance with accounting standards that should be and by using SDLC (System Development Life Cycle) theory. The samples used in this study were hospital employees associated with existing drug procurement procedures and medical devices using Non-probability Sampling. The types of data used are qualitative data and quantitative data sourced from primary data and secondary data. The results of this study stated that the Hospital has implemented procedures for procurement of medicines and medical devices tailored to the needs of hospitals. However, overall the procedure applied still has weaknesses and has not run effectively and efficiently in accordance with the standards of the procedure that should be. Therefore, the development of existing inventory cycle accounting information system to minimize risks and losses that may occur in hospitals. In addition, the hospital management needs to reform the procedures applied such as conducting training on new employees related to the company's accounting information system to establish the authority and responsibilities related to the procurement of drugs and equipment of the Hospital.